Buck-boost converter for PV solar system - Mohd Firdaus, Zainal Abidin (2016)
The PV solar system is a promising technology of harnessing renewable energy to be used in this world. However, the major drawback of PV solar system is the output generated is fluctuated within time. Thus, the buck-boost converter with arduino microcontroller used to regulate the voltage output from the solar panel. The arduino microcontroller is instructed to control the desired voltage output.